A new high-altitude species of centipede from the Andes of Ecuador (Chilopoda, Geophilomorpha, Schendylidae) - Pereira, Luis Alberto (Zootaxa, 2018)
Pectiniunguis aequatorialis sp. nov. (Chilopoda: Geophilomorpha: Schendylidae) is described and illustrated on the basis of specimens collected in the Cayambe-Coca Ecological Reserve in the High Andes of Ecuador. The new species is characterized by having ventral pore-fields on the anterior region of the trunk only, a trait that is shared by a single Neotropical congener: Pectiniunguis ascendens Pereira, Minelli & Barbieri, 1994 to which it is similar and is compared taxonomically. This is only the second report of a species of the genus Pectiniunguis Bollman, 1889 from mainland Ecuador. The other taxon is Pectiniunguis roigi Pereira, Foddai & Minelli, 2001, so far only known from the type locality, Limoncocha (Sucumbíos Province), and herein reported for the first time from Parque Nacional Sumaco Napo-Galeras (Napo Province).